Induced neural stem cells ameliorate blood-brain barrier injury by modulating the calcium signaling pathway of astrocyte in cerebral ischemia-reperfusion rats - Liang, Xueyun; Cao, Chuanshang; Liu, Ningmei; Chen, Dongmei; Liu, Ting; Ma, Haibin; Liu, Jiaxin; Wu, Taojuan; Niu, Jianguo (Frontiers in Cell and Developmental Biology, 2025)
BackgroundNeural stem cells offer new hope for ischemic stroke patients on the basis of their potential to reverse neurological sequelae, but it is still difficult to obtain sufficient neural stem cells in the clinic. We induced human placental mesenchymal stem cells to neural stem cells (iNSCs), the therapeutic effects and possible mechanisms of iNSCs in ischemic stroke were observed in this study.ResultsTransplanted iNSCs improved neurological deficits, increased the integrity of blood-brain barrier (BBB) structure and its related proteins expression level in middle cerebral artery occlusion/reperfusion (MCAO/R) rats. The in vitro study demonstrated that iNSCs treatment inhibited Ca2+ influx in oxygen-glucose deprived (OGD)-damaged astrocytes. Additionally, iNSCs downregulated the expression level of pCaMK-II, increased the expression level of superoxide dismutase, and inhibited the expression of caspase 9 in both brain of MCAO/R rats and OGD-damaged astrocytes.ConclusioniNSCs transplantation improved BBB function by modulating calcium signaling pathway of astrocyte in MCAO/R rats, which proved iNSCs may be a new promising neural stem cells origin for the treatment of cerebral ischemia-reperfusion injury.